ASPEK SOSIAL EKONOMI PENGUSAHAAN SAGU DI MALUKU - R Supriadi; lsmatul Hakim (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
In the province of Maluku, sago was and is still considered an essential staple food for the local people. Sago flour is consumed either for sustenance needs or as a commercial commodity. For industrial needs, sago is processed to become raw material for food, textile, wood adhesive, fodder, cosmetics, pharmaceuticals, pesticides, chemicals and others. This paper described several socio-economic indicators in sago related activities as a research result in Maluku.fl is concluded that, in general, the education level of respondents are primary school. Most of them have already a long time ago experience in harvesting of sago trees at least for 7 years. They inherit their land ownershif from their ancestors, and the average family land use patterns consist of 54.32 m2 for house building/construction, 966.36 m2 for home garden, and 2.88 hectares for sago garden.The income distribution among several activities of the farmers (respondents) is as followed :